Assessment of the Antifungal Activity of PMMA-MgO and PMMA-Ag Nanocomposite - Arf, Awder Nuree; kareem, Fadil Abdullah; Khdir, Younis Khalid; Zafar, Muhammad Sohail (Kurdistan Journal of Applied Research, 2024)
Orthodontic acrylic resin is used in the construction of orthodontic appliances. It lacks antimicrobial properties and is prone to microbial infection. So, the infection associated with it can be reduced via modification of orthodontic acrylic resin with nanoparticles (NPs) incorporation. The study directed to evaluate the antifungal properties of modified orthodontic acrylic resin incorporated with magnesium oxide (MgO)-NPs and silver (Ag)-NPs. NPs were mixed with polymethylmethacrylate (PMMA) in ethanol-assisted mixing method. Disc samples (10 mm in diameter and 2 mm thick) of PMMA-MgO, PMMA-Ag nanocomposites and PMMA alone (as control) were prepared. Then, C. albicans was isolated and identified clinically through taking swabs from acrylic denture base orthodontic appliances, cultured on a Sabouraud Dextrose Agar medium, followed by transferring on HiCrome™ candida Differential agar which is a selective and differential medium to distinguish distinct Candida species. The polymerase chain reaction was performed and the amplicon was separated by 2% gel electrophoresis and then visualised by ethidium bromide. DNA sequencing was performed on the sample at Sanger sequencing/ ABI 3500. Antifungal activity of PMMA-MgO and PMMA-Ag (1%, 3% and 5% of NPs) was conducted through disc diffusion assay and colony forming unit counts. The result showed a decrease in the number of adhered Candida albicans (C. albicans) of all concentrations of both nanocomposite and the decrease was statistically significant (P<0.05) in all experimental groups except MgO-NPs 1% and 3%. Increasing the concentration of NPs was associated with decrease in the adhered C. albicans. It was concluded that PMMA-MgO and PMMA-Ag nanocomposites showed anti-adherence activities against clinically isolated C. albicans in concentration dependent manner.